PERLINDUNGAN HUKUM BAGI ANAK YANG BERHADAPAN DENGAN HUKUM DALAM SISTEM PERADILAN PIDANA DI INDONESIA (SUATU TINJAUAN NORMATIF) - Jeanne Darc N Manik; Fauzi Amriuddin (Legal Spirit, 2017)
Special protection for children in conflict with the law covers children in conflict with the law; and children becoming the victims of crimes, are the duty and responsibility of the government and the community. The components of the criminal justice system is a subsystem of criminal justice, the police agencies, prosecutors, courts and prisons, and even can be added here is the legal counsel and public institutions. Legal protection for children in conflict with the law includes the treatment of children as human beings with their dignity and rights, the provision of companions special for children early, the provision of special facilities, the application of sanctions appropriate to the best interests of the children, monitoring and recording continuously on the development of children in conflict with the law, the provision of guarantees to maintain relationships with their parents or family and the protection of identity through the news media and to avoid labeling. Key Words: Protection, Child, Law, Criminal Justice System